Knowledge and Perceptions of Stakeholders on the National Dental Commission Act, 2023 in India: A Cross-sectional Study - Gadde Praveen; Anitha Akkaloori; Divvi Anusha; Shivashankar Kengadaran; Kalava Bhavana; Anil Budumuru (Journal of Indian Association of Public Health Dentistry)
Background: The gazette of the National Dental Commission (NDC) Act was recently published on August 11, 2023, and no studies were conducted to assess knowledge and perceptions about the act. Objectives: The objective of this study was to assess knowledge and perceptions among dental students, academicians, and practitioners about the NDC Act, 2023 in India. Materials and Methods: A cross-sectional survey was conducted using Google Forms between August and September 2024. Data were collected using a well-designed and pretested questionnaire. The questionnaire had three sections. Section A had demographic details. Section B gathered participants’ awareness of the key provisions of the act. Section C consisted of questions to assess participants’ perceptions about the act. The data were subjected to statistical analysis. Results: In total, 493 participants responded to the survey. Of these, 56.6% of the participants were aware of the act. The majority of the participants agreed that the act would be an improvement over the previous dental regulatory body and would result in positive changes in dental education and practice. However, 60.2% of the participants were uncertain about whether the NDC would operate with sufficient autonomy and independence in decision-making. The National Exit Test (Dental) was perceived as the ideal method to get a practicing license and to apply for postgraduate courses by 68.8% of the participants. Conclusions: Dental professionals lack adequate knowledge about the NDC Act of 2023. The findings highlight both the positive and negative perceptions toward the NDC.